Ferrocene-linked thymine/uracil conjugates: base pairing directed self-assembly and supramolecular packing - Patwa, Amit N.; Gupta, Susmita; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2008)
Ferrocene-linked bis(nucleobase) (la-c) and chimeric nucleobase (1d) conjugates have been synthesized from mono- and bis(hydroxybutyl)ferrocene 6 via Mitsunobu reaction as the key step. X-ray crystallographic studies of ferrocene bis(nucleobase) conjugates reveal two-dimensional supramolecular organizations of backbones through self-assembled Watson-Crick and reverse Watson-Crick type pairs. Ferrocene-bis(thymine) conjugate self-assembles by reverse Watson-Crick pairing, while the corresponding bis(uracil) conjugate self-assembles by alternating WC and reverse WC type pairing. Such continuous assemblies are not seen in monosubstituted ferrocene nucleobase conjugates which form only planar sheets. The results are interesting from the point of understanding and engineering supramolecular assemblies through rational design of base pairing patterns.

Ferrocene-Bis(thymine/uracil) conjugates: base pairing directed, spacer dependent self-assembly and supramolecular packing - Patwa, Amit N.; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2010)
X-ray crystallographic studies of methylene linked Ferrocene-bis(thymine/uracil) conjugates Fc(T:T)m and Fc(U:U)(M) reveal base dependent 2-D supramolecular assemblies generated via wobble self-pairing for bis-thymine and reverse wobble self-pairing for bis-uracil conjugates, differing in architecture from the corresponding butylene spacer linked conjugates